Estimating the portion of technical analysts in a market. Issue 41 (2nd September 2017) - Cook, Jonathan
ABSTRACT: This article presents structural estimates of the portion of technical analysts in six markets. I find that the portion of technical analysts in the U.S. equity market has been decreasing since the 1970s. A simple asset pricing model predicts that both risk and return are increasing in the portion of technical analysts. This prediction is confirmed across stock market indexes for six countries.